2018
DOI: 10.1155/2018/5757434
|View full text |Cite
|
Sign up to set email alerts
|

Malignant Spinal Cord Compression Syndrome as an Initial Presentation of Testicular Cancer

Abstract: Malignant spinal cord compression syndrome (MSCCS) occurs in 2.5 to 5% of all oncological patients. In 20% of the cases, it is the initial manifestation. This syndrome is a rare event among germ cell tumors (GCT), occurring in only 1.7% of the patients. We present the case of a 24-year-old man who arrived at the emergency department with dysesthesia and paraparesis as well as urinary incontinence. Imaging studies showed an infiltrative lesion in the left testicle, pulmonary and hepatic metastatic disease, and … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2021
2021
2021
2021

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 17 publications
0
1
0
Order By: Relevance
“…Epidemiological studies have reported that MSCC could be the initial presentation of malignancy up to 20%, [3][4][5] and it can occur in any cancer type. [10][11][12] Regardless of whether the site of the primary cancer is known or not, surgery does play a role in spinal metastases management because MSCC is an oncological emergency that necessitates immediate surgical intervention. According to a recent review, an integrated multidisciplinary approach is needed for the management of spinal metastases due to its complexity.…”
Section: Discussionmentioning
confidence: 99%
“…Epidemiological studies have reported that MSCC could be the initial presentation of malignancy up to 20%, [3][4][5] and it can occur in any cancer type. [10][11][12] Regardless of whether the site of the primary cancer is known or not, surgery does play a role in spinal metastases management because MSCC is an oncological emergency that necessitates immediate surgical intervention. According to a recent review, an integrated multidisciplinary approach is needed for the management of spinal metastases due to its complexity.…”
Section: Discussionmentioning
confidence: 99%